KEBIJAKAN PEMERINTAH DESA MARGOMULYO DALAM MENGELOLA HARMONI MASYARAKAT SUKU BALI DAN SUKU JAWA DI KABUPATEN LUWU TIMUR - Wulandari, Meli; Abdain (Datuk Sulaiman Law Review (DaLRev), 2024)
This study aims to examine the social relations between the Balinese and Javanese ethnic groups in Margomulyo Village, in order to establish a harmonious relationship through the policies implemented by the Margomulyo Village government, East Luwu Regency. This research adopts an empirical legal research methodology. The results of the study indicate that the social relations between the Balinese and Javanese communities in Margomulyo Village are well-maintained, with the Javanese being the majority population. The current leadership (Village Head) is also from the Javanese ethnic group; however, this has not resulted in any disparity in rights between the Balinese and Javanese groups. The policies implemented in Margomulyo Village focus on facilitating the community in creating a socially cohesive environment, maintaining a clean and healthy living environment, ensuring public order, and resolving disputes through familial (amicable) means.